Mobile Applications in Urban Ecotourism: Promoting Digitization and Competitive Differentiation - Cardoso, Ana (2022)
This article outlines the mobile and digital advances on urban ecotourism, acknowledging some ground-breaking projects around the world. On top of providing a broad perspective on general concepts related to urban ecotourism and its benefits, it also presents a revision of the value of urban green spaces in the environmental, economic and socio-cultural dimensions.